The resource availability hypothesis (RAH) and cross-cultural patterns: which one explains West African Cochlospermum species’ uses in Benin? - Gnimansou Abraham, Favi; Gbèwonmèdéa Hospice, Dassou; Djidohokpin, Donald; Marie‑Ange Sènamie Ouachinou, Jéronime; Chabi, Ghyslain Kpétikou; Gbedolo, Eutiche; Anagonou, Alain; Hidalgo-Triana, Noelia; Cossi Adomou, Aristide (BMC Springer Nature, 2022)
Benin, widely used Cochlospermum tinctorium and C. planchonii as food, medicine,etc. Unfortunately, the uncontrolled harvest of their rootstocks exposes them to local extension risk. This study aimed to (i) assess the use forms, use values, abundance and perceived spatiotemporal dynamics, (ii) determine how does local abundance or cultural patterns afect the use of Cochlospermum species, and (iii) assess local harvesting modes. 756 Dialog Partners through 27 ethnic groups were questioned countrywide using semistructured interviews. Questions refer to local taxonomy, specifc uses, organs sought, harvesting modes and local conservation strategies; afterward, local abundance of each species was assessed. Ethnobotanical indicators were analyzed. Comparison tests and statistical analyses were performed. C. tinctorium and C. planchonii are locally well known and involved into 83 specifc uses, grouped into ten categories of which medicinal use was the main. The use values of C. planchonii (0.10±0.19) and C. tinctorium (0.23±0.20) varied signifcantly between the ethnic groups, and only C. tinctorium showed index of commercially value above 75% for some ethnic groups. The current abundance, about 84 and 97 tufts.ha−1, respectively, for C. planchonii and C. tinctorium was perceived with a decline of 81.09% (C. tinctorium) and 73.7% (C. planchonii) of informants. Moreover, the Spearman’s correlation and Kruskal–Wallis tests performed revealed that the use values of C. tinctorium and C. planchonii were signifcantly correlated on the one hand with their local abundance and on the other hand with the investigated ethnic groups. About 42.3% of women produced the powder as principal activity, while more than 57% produced it mainly at the end of farm work. However, the conservation management was practiced by very few informants and consisted of partial harvesting of rootstocks (41.8%, only in southern Benin), and fallowing of harvesting areas (3.97%, only in northern Benin).
Keywords: Agricultura - Benin; Cochlospermum spp.; Cultural importance